2017
DOI: 10.5114/jcb.2017.69809
|View full text |Cite
|
Sign up to set email alerts
|

Focal therapy for prostate cancer: the technical challenges

Abstract: Focal therapy for prostate cancer has been proposed as an alternative treatment to whole gland therapy, offering the opportunity for tumor dose escalation and/or reduced toxicity. Brachytherapy, either low-dose-rate or high-doserate, provides an ideal approach, offering both precision in dose delivery and opportunity for a highly conformal, non-uniform dose distribution. Whilst multiple consensus documents have published clinical guidelines for patient selection, there are insufficient data to provide clear gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Our team has a particular interest in biologically optimised focal therapy that applies a non‐uniform distribution of radiation dose in an effort to maximise tumour control and limit side‐effects through minimising irradiation of normal tissues. The role of PSMA PET in this scenario is to improve the overall sensitivity and specificity of a model to spatially define the biological characteristics of tumours to inform the treatment planning process . However, the registration framework we have developed is generalisable and could be applied in many diagnostic and theragnostic applications .…”
Section: Discussionmentioning
confidence: 99%
“…Our team has a particular interest in biologically optimised focal therapy that applies a non‐uniform distribution of radiation dose in an effort to maximise tumour control and limit side‐effects through minimising irradiation of normal tissues. The role of PSMA PET in this scenario is to improve the overall sensitivity and specificity of a model to spatially define the biological characteristics of tumours to inform the treatment planning process . However, the registration framework we have developed is generalisable and could be applied in many diagnostic and theragnostic applications .…”
Section: Discussionmentioning
confidence: 99%
“…Although prostate cancer is mostly a multi-focal disease [ 3 ], recent evidence indicates that focal therapy delivered to the index lesion, the largest tumor focus within the prostate, may effectively control disease. Thus, this is a new radical treatment for low- and intermediate-risk prostate cancer [ 4 , 5 , 6 , 7 , 8 ]. Several modalities, such as high-intensity focused ultrasound, cryotherapy, laser ablation, and photodynamic therapy have been developed to facilitate focal therapy [ 5 ].…”
Section: Purposementioning
confidence: 99%
“…In focal therapy, permanent prostate brachytherapy using 125 I can be an effective option for prostate cancer [ 6 , 7 ]. It has been reported that focal brachytherapy may reduce acute morbidity, because dose reductions during whole-gland prostate brachytherapy were associated with reduced acute urinary morbidity [ 9 ].…”
Section: Purposementioning
confidence: 99%
“…However, limitations in imaging accuracy preclude the correct evaluation of the number and extension of prostate cancer target lesions [ 15 ]. In focal brachytherapy, there are certain technical challenges in application of this modality due to insufficient data of clear guidelines on isotope selection, target delineation, treatment planning, dose prescription, and treatment delivery [ 21 ]. Furthermore, there are significant concerns regarding the possibility of undertreatment of the rest of the gland due to non-visible lesions and unavoidable sampling errors in prostate biopsy related to the multifocal nature of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%